Breathable medicine : pulmonary mode of drug delivery - Gandhimathi, Chinnasamy (2015)
Pharmaceutically active compounds require different modes of drug delivery systems to accomplish therapeutic activity without loss of its activity and lead to exhibit no adverse effects. Originating from ancient days, pulmonary mode of drug delivery is gaining much importance compared to other modes of drug delivery systems with respect to specific diseases. Pulmonary drug delivery is a non-invasive route for local and systemic therapies together with more patient convenience, compliance and is a needleless system. In this review, we addressed the vaccine delivery via nonor minimally invasive routes. Polymeric nanoparticles are preferred for use in the pulmonary delivery devices owing to a prolonged retention in lungs. Small site for absorption, mucociliary clearance, short residence time and low bioavailability are some of the limitations in pulmonary drug delivery have been resolved by generating micro- and nano-sized aerosol particles. We have classified the breathable medicine on the basis of available devices for inhalation and also prominent diseases treated through pulmonary mode of drug delivery. Owing to increasing toxicity of pharmacological drugs, the use of natural medicines has been rapidly gaining importance recently. The review article describes breathability of medicines or the pulmonary mode of drug delivery system and their drug release profile, absorption, distribution and efficacy to cure asthma and diabetes.